Social imaginaries of the entrepreneur in Central America. An approach to competitiveness and social responsibility - Pérez Sáinz, Juan Pablo (2017)
This paper analyzes the social representations of Central American entrepreneurs. To do this, take two examples into account. The first is related to the image of society included in the agenda for competitiveness and sustainable development developed in 1999 by the Central American Institute of Business Administration (INCAE). This agenda proposes a model of social action in which the entrepreneur appears as the key actor. The second example refers to the so-called "corporate social responsibility" and, in empirical terms, has taken as a reference the Center of Action of Corporate Responsibility (CentraRSE) of Guatemala. It concludes with some reflections on how the Central American entrepreneurs, through its new organic intellectuals, imagines the social in the region.